2000
DOI: 10.1007/s11661-000-0290-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nanostructured Cr3C2-25(Ni20Cr) coatings

Abstract: On the basis of the nanocrystalline Cr 3 C 2 -25 (Ni20Cr) feedstock powders produced by mechanical milling, a nanostructured coating has been synthesized using high velocity oxygen fuel (HVOF) thermal spraying. The properties of the nanostructured coating were compared to those of the conventional coating of the same composition using scanning electron microscope (SEM), transmission electron microscope (TEM), and microhardness tests. The nanostructured Cr 3 C 2 -25 (Ni20Cr) coating synthesized in this study ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 17 publications
0
39
0
Order By: Relevance
“…In the last few decades, several kinds of coatings have been developed using nanocrystalline materials. Chromium carbide based coatings are used to protect components exposed to severe conditions in a number of industries [11][12][13][14] . A variety of techniques have been used to prepare chromium carbide based coatings and the high velocity oxygen fuel (HVOF) process is widely used, as it produces smooth, low porosity, dense and adherent coatings, without altering significantly the integrity of the carbide particles 11,15,16 .…”
mentioning
confidence: 99%
“…In the last few decades, several kinds of coatings have been developed using nanocrystalline materials. Chromium carbide based coatings are used to protect components exposed to severe conditions in a number of industries [11][12][13][14] . A variety of techniques have been used to prepare chromium carbide based coatings and the high velocity oxygen fuel (HVOF) process is widely used, as it produces smooth, low porosity, dense and adherent coatings, without altering significantly the integrity of the carbide particles 11,15,16 .…”
mentioning
confidence: 99%
“…The abrasion resistance of thermal sprayed coatings is related to the relative fracture toughness. 14) The indentation fracture method is employed here to characterize the relative fracture toughness of both the HVAF sprayed nanostructured and conventional NiCrC coatings. Under a load of 5 N, no crack was found in either of the coatings.…”
Section: Resultsmentioning
confidence: 99%
“…The indentation fracture method has been used to obtain information about the relative fracture toughness of coatings 29 . In this study, at 1000 g hardness test load, cracks emanating from the indents were observed in both types of coatings.…”
Section: Discussionmentioning
confidence: 99%